Women in politics : Portugal as a case study - Galito, Maria Sousa (2018)
Democracy is about the power of people and women are majoritarian in society, therefore, they have been claiming for more rights and more representativeness in politics for a long time. After running for office, some have become political representatives only by merit and constant struggle. Others got their chance after the legalization of female quotas and targets. The system has gone a long way since ladies were recognized the right to vote. The evolution of women’s empowerment is the focus of this paper that tries to analyze the main characteristics, causes and effects of this process, based on theory and world references or statistics. Portugal was chosen as a case study for not being much researched or not sufficiently so far.